Reading the Bible with Richard Hooker. - Eppley, Daniel (Minneapolis : Fortress Press, 2016)
Many of the divisions facing Christians today include disagreements over the interpretation of Scripture. These disagreements arise not only regarding the meaning of particular biblical passages, but also involve different approaches to determining how the meaning of Scripture is discerned. Such disagreement over the interpretation of Scripture is nothing new. Insights available from past efforts to resolve disputes over interpretation can be a valuable resource for modern efforts to facilitate intra-Christian dialogue. This study elucidates the biblical hermeneutic championed by Richard Hooker, a formative figure of the Anglican tradition, to recommend it as a resource for modern Christians. In his approach to interpreting Scripture, Hooker recognizes the importance of both rational reflection and inspired insight while also treading a middle path that balances the respect due to interpretive authorities against the responsibilities of the individual conscience. These and other elements of Hookers hermeneutic make it a valuable resource for those who seek to promote dialogue and reconciliation in a divided church.
Introduction -- Scoundrels and Fools: Biblical Hermeneutics in Elizabethan England -- The Puritan Othello: Shakespeare and Hooker on the Dangers of Certainty -- Beyond a Reasonable Doubt: Private and Public Reason in Hooker's Hermeneutic -- Dissent without Disloyalty: The Role of Private Interpretation of Scripture in Hooker's Public Hermeneutic -- Reasons of the Heart: Hermeneutics and Assurance -- Conclusion -- Synopsis of Othello.
Keywords: Hooker, Richard, -- 1553 or 1554-1600.; Bible -- Hermeneutics; Bible -- Criticism, interpretation, etc. -- History; Anglican Communion -- Doctrines; Church history; Reformation